Abdominal paracentesis drainage attenuates intestinal inflammation in rats with severe acute pancreatitis by inhibiting the HMGB1-mediated TLR4 signaling pathway - Huang, Shang-Qing (World J Gastroenterol, 2021)
BACKGROUND: Our previous studies confirmed that abdominal paracentesis drainage (APD) attenuates intestinal mucosal injury in rats with severe acute pancreatitis (SAP), and improves administration of enteral nutrition in patients with acute pancreatitis (AP). However, the underlying mechanisms of the beneficial effects of APD remain poorly understood. AIM: To evaluate the effect of APD on intestinal inflammation and accompanying apoptosis induced by SAP in rats, and its potential mechanisms. METHODS: SAP was induced in male adult Sprague-Dawley rats by 5% sodium taurocholate. Mild AP was induced by intraperitoneal injections of cerulein (20 μg/kg body weight, six consecutive injections). Following SAP induction, a drainage tube connected to a vacuum ball was placed into the lower right abdomen of the rats to build APD. Morphological changes, serum inflammatory mediators, serum and ascites high mobility group box protein 1 (HMGB1), intestinal barrier function indices, apoptosis and associated proteins, and toll-like receptor 4 (TLR4) signaling molecules in intestinal tissue were assessed. RESULTS: APD significantly alleviated intestinal mucosal injury induced by SAP, as demonstrated by decreased pathological scores, serum levels of D-lactate, diamine oxidase and endotoxin. APD reduced intestinal inflammation and accompanying apoptosis of mucosal cells, and normalized the expression of apoptosis-associated proteins in intestinal tissues. APD significantly suppressed activation of the intestinal TLR4 signaling pathway mediated by HMGB1, thus exerting protective effects against SAP-associated intestinal injury. CONCLUSION: APD improved intestinal barrier function, intestinal inflammatory response and accompanying mucosal cell apoptosis in SAP rats. The beneficial effects are potentially due to inhibition of HMGB1-mediated TLR4 signaling.